Low-carbon aluminum silicon carbide brick for ladle and preparation method of low-carbon aluminum silicon carbide brick
By using dense corundum and cyanite with specific particle size distribution in aluminum silicon carbide bricks, and introducing graphite, graphene oxide, metal silicon powder, lanthanum oxide and zirconium carbide as additives, the problem of oxidation of aluminum silicon carbide bricks at high temperatures is solved, and the high performance and long life of low-carbon aluminum silicon carbide bricks are achieved.
Patent Information
- Application Number
- CN202411794342.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing aluminum silicon carbide carbon bricks are prone to oxidation at high temperatures, resulting in structural damage, hole formation and disintegration, thereby shortening the service life of the molten iron bag and increasing maintenance costs.
Deep corundum and cyanite with specific particle size distribution are used, graphite and graphene oxide are used as carbon sources, and metal silicon powder, lanthanum oxide and zirconium carbide are introduced as additives to produce low-carbon aluminum silicon carbide bricks through specific preparation methods.
Low-carbon aluminum silicon carbide bricks have low porosity, excellent oxidation resistance, corrosion resistance, slag resistance and good thermal shock stability, extending the service life of the molten iron bag and reducing maintenance costs.
Smart Images

Figure BDA0005176259950000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a low-carbon aluminum silicon carbide brick for an iron ladle and a preparation method thereof. Background Art
[0002] Aluminum silicon carbide carbon brick is a kind of unfired product formed by high temperature. Most aluminum silicon carbide carbon bricks use corundum, silicon carbide and graphite as the main raw materials, and add appropriate amount of additives. They are mainly used for the lining of ladles and torpedo tanks. As a special equipment for storing and transporting molten iron, the ladle has always played a vital role in the ironmaking industry, and the performance of the refractory material of the ladle lining will directly affect the quality and service life of the ladle. With the continuous development of the ironmaking industry, people have higher requirements for ladle bricks.
[0003] Since the ladle works under the alternating state of high temperature and low temperature, the inner lining of the ladle is very easy to be corroded and peeled off under the continuous flushing of molten iron, which will shorten the service life of the ladle and increase the maintenance cost. Since aluminum silicon carbide carbon bricks are carbon-containing refractory materials, they are easily oxidized at high temperatures. After oxidation, the structure of aluminum silicon carbide carbon bricks will be destroyed, holes and falling off will appear, and the disintegration of aluminum silicon carbide carbon bricks will be accelerated. At the same time, when the structure of the brick body is destroyed and disintegrated, its excellent thermal shock stability will also be lost. Therefore, it is urgent to develop an aluminum silicon carbide carbon brick that is resistant to oxidation, erosion and has good thermal shock stability. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a low-carbon aluminum silicon carbide brick for a ladle and a preparation method thereof in view of the shortcomings of the prior art. Dense corundum and kyanite with a specific particle size distribution are used, graphite and graphene oxide are selected as carbon sources, and metallic silicon powder, lanthanum oxide and zirconium carbide are introduced as additives. The low-carbon aluminum silicon carbide brick finally produced has a lower porosity, excellent anti-oxidation, anti-corrosion, anti-slag performance and good thermal shock stability.
[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a low-carbon aluminum silicon carbide brick for an iron ladle, comprising the following raw materials in parts by weight: 40 to 60 parts of dense corundum, 10 to 20 parts of kyanite, 5 to 15 parts of silicon carbide, 3 to 6 parts of graphite, 3 to 6 parts of graphene oxide, 0.5 to 2 parts of metallic silicon powder, 0.5 to 2 parts of lanthanum oxide, 1 to 4 parts of zirconium carbide and 4 to 7 parts of phenolic resin.
[0006] In the above scheme, the dense corundum includes the following mass proportions of dense corundum of different particle sizes: 10 to 15 parts of dense corundum with a particle size of 5 to 3 mm, 10 to 15 parts of dense corundum with a particle size of 3 to 1 mm, 10 to 15 parts of dense corundum with a particle size of 1 to 0.1 mm, and 10 to 15 parts of dense corundum with a particle size of 200 to 250 mesh.
[0007] In the above scheme, the kyanite includes the following kyanite of different particle sizes in the following mass proportions: 3 to 6 parts of kyanite with a particle size of 3 to 1 mm, 3 to 6 parts of kyanite with a particle size of 1 to 0.1 mm, and 4 to 8 parts of kyanite with a particle size of 200 to 250 mesh.
[0008] In the above scheme, the Al2O3 content in the dense corundum is ≥97wt%.
[0009] In the above scheme, the sum of the Al2O3 and SiO2 contents in the kyanite is ≥98wt%.
[0010] In the above solution, the SiC content in the silicon carbide is ≥ 98wt%.
[0011] In the above scheme, the particle size of the silicon carbide is 100-120 mesh.
[0012] In the above scheme, the particle size of the graphite is 180-200 meshes.
[0013] In the above scheme, the particle size of the graphene oxide is 180 to 200 meshes.
[0014] In the above scheme, the particle size of the metallic silicon powder is 180-200 meshes.
[0015] In the above scheme, the particle size of the lanthanum oxide is 260-300 meshes.
[0016] In the above scheme, the particle size of the zirconium carbide is 80-100 meshes.
[0017] The present invention also provides a method for preparing low-carbon aluminum silicon carbide bricks for a ladle, comprising the following steps:
[0018] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and phenolic resin to 40-50° C. respectively;
[0019] 2) adding dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer and stirring once, and then adding dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and phenolic resin and stirring twice to obtain a mixed mud;
[0020] 3) The mixed mud is pressed into shape to obtain a brick blank, which is then baked and solidified to obtain a low-carbon aluminum silicon carbide brick for a ladle.
[0021] In the above scheme, the stirring rate of the mixer is 970-1000 r / min, the first stirring time is 4-6 min, and the second stirring time is 10-15 min.
[0022] In the above scheme, the bulk density of the brick is 2.65-2.75 g / cm 3 .
[0023] In the above scheme, the baking and curing temperature is 200-240° C. and the time is 18-24 hours.
[0024] In the above scheme, the apparent porosity of the low carbon aluminum silicon carbide brick is 8.1-8.5%, and the bulk density is 2.84-2.90 g / cm 3 The room temperature compressive strength is 54.6~58.9MPa, the softening start temperature under 0.2MPa load is 1475~1490℃, and the thermal shock stability (1100℃ water cooling) is 6~8 times.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention is based on the demand for improving the oxidation resistance, corrosion resistance, slag resistance and thermal shock stability of low-carbon aluminum silicon carbide bricks. It uses dense corundum and kyanite with a specific particle size distribution, selects graphite and graphene oxide as carbon sources, and introduces metal silicon powder, lanthanum oxide and zirconium carbide as additives:
[0027] First, the surface of graphene oxide contains a large number of oxygen-containing functional groups and has excellent antioxidant properties; lanthanum oxide has efficient catalytic properties and can convert carbon and sulfur in molten iron into carbon dioxide and sulfur dioxide respectively through a series of adsorption and desorption reactions, thereby improving the quality of iron products. It can also promote the conversion of carbon monoxide in molten iron into carbon dioxide, reduce potential safety hazards in the ironmaking process, and reduce harm to human health;
[0028] At the same time, there is a synergistic effect between graphene oxide and lanthanum oxide. At high temperatures, lanthanum oxide can form complexes with the carboxyl groups in graphene oxide in various ways. This complex has strong structural stability. Since graphene oxide has a very large specific surface area, the lanthanum oxide coordinated with it is evenly dispersed in it, and can also obtain a larger specific surface area and have more adsorption sites, thereby having stronger catalytic activity and improving catalytic efficiency.
[0029] However, at the oxygen-rich interface (such as the interface between molten iron and molten iron ladle), lanthanum oxide will also promote the oxidation of graphite, another carbon source in low-carbon aluminum-carbon bricks. Therefore, by controlling the amount of lanthanum oxide and using graphene oxide with strong antioxidant ability to cooperate with it, the direct contact area between lanthanum oxide and graphite is greatly reduced to prevent the oxidation of the carbon source in the material.
[0030] In addition, the polymer complex formed by lanthanum oxide and graphene oxide has strong strength and is evenly dispersed in the matrix, which greatly reduces the stress generated when the volume of the refractory changes, inhibits the growth and aggregation of microcracks, improves the strength and structural stability of the refractory, and enhances the crack resistance of the refractory.
[0031] Zirconium carbide has extremely high hardness and melting point, which can enhance the thermal shock stability of the material. The addition of zirconium carbide can also increase the density of the material, reduce the porosity, and improve the material's oxidation resistance. In addition, kyanite will form a softer and more viscous siliceous liquid phase at high temperatures. When combined with zirconium carbide with an extremely low thermal expansion coefficient, it will produce heterogeneous dispersion strengthening and toughening, further improving the strength and toughness of the material.
[0032] Through the combined effect of the above ingredients, the low-carbon aluminum silicon carbide bricks finally produced have low porosity, excellent anti-oxidation, anti-corrosion, anti-slag properties and good thermal shock stability. As the lining material of the ladle, it can not only effectively reduce the energy consumption of ironmaking, but also has a long service life. DETAILED DESCRIPTION
[0033] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0034] In the following embodiments, the Al2O3 content in dense corundum is ≥97wt%; the sum of the Al2O3 and SiO2 contents in kyanite is ≥98wt%; the particle size of silicon carbide is 100-120 mesh, and the SiC content is ≥98wt%; the particle size of graphite is 180-200 mesh; the particle size of graphene oxide is 180-200 mesh; the particle size of metallic silicon powder is 180-200 mesh; the particle size of lanthanum oxide is 260-300 mesh; and the particle size of zirconium carbide is 80-100 mesh.
[0035] Example 1
[0036] The low-carbon aluminum silicon carbide bricks used for the ladle in this embodiment include the following raw materials in parts by mass:
[0037] 12 parts of dense corundum with a particle size of 5-3mm, 13 parts of dense corundum with a particle size of 3-1mm, 12 parts of dense corundum with a particle size of 1-0.1mm, 13 parts of dense corundum with a particle size of 200-250 mesh, 4 parts of kyanite with a particle size of 3-1mm, 4 parts of kyanite with a particle size of 1-0.1mm, 5 parts of kyanite with a particle size of 200-250 mesh, 10 parts of silicon carbide, 4 parts of graphite, 5 parts of graphene oxide, 1 part of metallic silicon powder, 1 part of lanthanum oxide, 2 parts of zirconium carbide, and 5 parts of thermosetting phenolic resin.
[0038] The method for preparing low-carbon aluminum silicon carbide bricks for a ladle in this embodiment comprises the following steps:
[0039] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and thermosetting phenolic resin to 40-50° C. respectively;
[0040] 2) Add dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer with a rotation speed of 970 to 1000 r / min and stir for 4 to 6 minutes, then add dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and thermosetting phenolic resin and stir for 10 to 15 minutes to obtain a mixed mud;
[0041] 3) The mixed mud is pressed into a brick by a press machine. The pressure of the press machine is 900t. The bulk density of the obtained brick is 2.71g / cm 3 The obtained bricks are baked and cured at 210°C for 18 hours, and taken out after naturally cooling to room temperature to obtain low-carbon aluminum silicon carbide bricks for ladles.
[0042] Example 2
[0043] The low-carbon aluminum silicon carbide bricks used for the ladle in this embodiment include the following raw materials in parts by mass:
[0044] 14 parts of dense corundum with a particle size of 5-3mm, 14 parts of dense corundum with a particle size of 3-1mm, 10 parts of dense corundum with a particle size of 1-0.1mm, 11 parts of dense corundum with a particle size of 200-250 mesh, 3 parts of kyanite with a particle size of 3-1mm, 4 parts of kyanite with a particle size of 1-0.1mm, 6 parts of kyanite with a particle size of 200-250 mesh, 10 parts of silicon carbide, 4 parts of graphite, 5 parts of graphene oxide, 1 part of metallic silicon powder, 1 part of lanthanum oxide, 2 parts of zirconium carbide, and 5 parts of thermosetting phenolic resin.
[0045] The method for preparing low-carbon aluminum silicon carbide bricks for a ladle in this embodiment comprises the following steps:
[0046] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and thermosetting phenolic resin to 40-50° C. respectively;
[0047] 2) Add dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer with a rotation speed of 970 to 1000 r / min and stir for 4 to 6 minutes, then add dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and thermosetting phenolic resin and stir for 10 to 15 minutes to obtain a mixed mud;
[0048] 3) The mixed mud is pressed into a brick by a press. The pressure of the press is 850t. The bulk density of the obtained brick is 2.69g / cm 3 The obtained bricks are baked and cured at 210°C for 21 hours, and taken out after naturally cooling to room temperature to obtain low-carbon aluminum silicon carbide bricks for ladles.
[0049] Example 3
[0050] The low-carbon aluminum silicon carbide bricks used for the ladle in this embodiment include the following raw materials in parts by mass:
[0051] 12 parts of dense corundum with a particle size of 5-3mm, 13 parts of dense corundum with a particle size of 3-1mm, 13 parts of dense corundum with a particle size of 1-0.1mm, 12 parts of dense corundum with a particle size of 200-250 mesh, 3 parts of kyanite with a particle size of 3-1mm, 4 parts of kyanite with a particle size of 1-0.1mm, 7 parts of kyanite with a particle size of 200-250 mesh, 8 parts of silicon carbide, 3 parts of graphite, 5 parts of graphene oxide, 2 parts of metallic silicon powder, 2 parts of lanthanum oxide, 4 parts of zirconium carbide, and 6 parts of thermosetting phenolic resin.
[0052] The method for preparing low-carbon aluminum silicon carbide bricks for a ladle in this embodiment comprises the following steps:
[0053] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and thermosetting phenolic resin to 40-50° C. respectively;
[0054] 2) Add dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer with a rotation speed of 970 to 1000 r / min and stir for 4 to 6 minutes, then add dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and thermosetting phenolic resin and stir for 10 to 15 minutes to obtain a mixed mud;
[0055] 3) The mixed mud is pressed into a brick by a press. The pressure of the press is 950t. The bulk density of the obtained brick is 2.75g / cm 3 The obtained bricks are baked and cured at 210°C for 22 hours, and taken out after naturally cooling to room temperature to obtain low-carbon aluminum silicon carbide bricks for ladles.
[0056] Example 4
[0057] The low-carbon aluminum silicon carbide bricks used for the ladle in this embodiment include the following raw materials in parts by mass:
[0058] 10 parts of dense corundum with a particle size of 5-3mm, 10 parts of dense corundum with a particle size of 3-1mm, 15 parts of dense corundum with a particle size of 1-0.1mm, 15 parts of dense corundum with a particle size of 200-250 mesh, 4 parts of kyanite with a particle size of 3-1mm, 3 parts of kyanite with a particle size of 1-0.1mm, 8 parts of kyanite with a particle size of 200-250 mesh, 9 parts of silicon carbide, 5 parts of graphite, 3 parts of graphene oxide, 0.5 parts of metallic silicon powder, 1 part of lanthanum oxide, 2 parts of zirconium carbide, and 5 parts of thermosetting phenolic resin.
[0059] The method for preparing low-carbon aluminum silicon carbide bricks for a ladle in this embodiment comprises the following steps:
[0060] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and thermosetting phenolic resin to 40-50° C. respectively;
[0061] 2) Add dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer with a rotation speed of 970 to 1000 r / min and stir for 4 to 6 minutes, then add dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and thermosetting phenolic resin and stir for 10 to 15 minutes to obtain a mixed mud;
[0062] 3) The mixed mud is pressed into a brick by a press machine with a pressure of 800t. The bulk density of the obtained brick is 2.66g / cm 3 The obtained bricks are baked and cured at 200°C for 18 hours, and taken out after naturally cooling to room temperature to obtain low-carbon aluminum silicon carbide bricks for ladles.
[0063] Example 5
[0064] The low-carbon aluminum silicon carbide bricks used for the ladle in this embodiment include the following raw materials in parts by mass:
[0065] 14 parts of dense corundum with a particle size of 5-3mm, 12 parts of dense corundum with a particle size of 3-1mm, 12 parts of dense corundum with a particle size of 1-0.1mm, 14 parts of dense corundum with a particle size of 200-250 mesh, 6 parts of kyanite with a particle size of 3-1mm, 6 parts of kyanite with a particle size of 1-0.1mm, 7 parts of kyanite with a particle size of 200-250 mesh, 7 parts of silicon carbide, 3 parts of graphite, 4 parts of graphene oxide, 1 part of metallic silicon powder, 2 parts of lanthanum oxide, 2 parts of zirconium carbide, and 6 parts of thermosetting phenolic resin.
[0066] The method for preparing low-carbon aluminum silicon carbide bricks for a ladle in this embodiment comprises the following steps:
[0067] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and thermosetting phenolic resin to 40-50° C. respectively;
[0068] 2) Add dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer with a rotation speed of 970 to 1000 r / min and stir for 4 to 6 minutes, then add dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and thermosetting phenolic resin and stir for 10 to 15 minutes to obtain a mixed mud;
[0069] 3) The mixed mud is pressed into a brick by a press machine. The pressure of the press machine is 900t. The bulk density of the obtained brick is 2.72g / cm 3 The obtained bricks are baked and cured at 190°C for 24 hours, and taken out after naturally cooling to room temperature to obtain low-carbon aluminum silicon carbide bricks for ladles.
[0070] Example 6
[0071] The low-carbon aluminum silicon carbide bricks used for the ladle in this embodiment include the following raw materials in parts by mass:
[0072] 11 parts of dense corundum with a particle size of 5-3mm, 11 parts of dense corundum with a particle size of 3-1mm, 11 parts of dense corundum with a particle size of 1-0.1mm, 12 parts of dense corundum with a particle size of 200-250 mesh, 5 parts of kyanite with a particle size of 3-1mm, 5 parts of kyanite with a particle size of 1-0.1mm, 4 parts of kyanite with a particle size of 200-250 mesh, 13 parts of silicon carbide, 6 parts of graphite, 3 parts of graphene oxide, 2 parts of metallic silicon powder, 1 part of lanthanum oxide, 3 parts of zirconium carbide, and 4 parts of thermosetting phenolic resin.
[0073] The method for preparing low-carbon aluminum silicon carbide bricks for a ladle in this embodiment comprises the following steps:
[0074] 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and thermosetting phenolic resin to 40-50° C. respectively;
[0075] 2) Add dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer with a rotation speed of 970 to 1000 r / min and stir for 4 to 6 minutes, then add dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and thermosetting phenolic resin and stir for 10 to 15 minutes to obtain a mixed mud;
[0076] 3) The mixed mud is pressed into a brick by a press machine with a pressure of 800t. The bulk density of the obtained brick is 2.65g / cm 3 The obtained bricks are baked and cured at 180°C for 20 hours, and taken out after naturally cooling to room temperature to obtain low-carbon aluminum silicon carbide bricks for ladles.
[0077] Comparative Example 1
[0078] The low carbon aluminum silicon carbide brick in this comparative example includes the following raw materials in parts by weight:
[0079] 10 parts of high alumina with a particle size of 5-3mm, 8 parts of high alumina with a particle size of 3-1mm, 8 parts of high alumina with a particle size of 1-0.1mm, 6 parts of high alumina with a particle size of 200-250 mesh, 5 parts of andalusite with a particle size of 3-1mm, 5 parts of andalusite with a particle size of 1-0.1mm, 7 parts of graphite with a particle size of 180 mesh, 10 parts of silicon carbide with a particle size of 200-250 mesh, 2 parts of metal iron powder with a particle size of 200-250 mesh, and 3 parts of thermosetting phenolic resin.
[0080] The preparation method of the low carbon aluminum silicon carbide brick in this comparative example comprises the following steps:
[0081] 1) adding high alumina, andalusite, graphite, silicon carbide, metal iron powder and thermosetting phenolic resin of various particle sizes into a mixer at a speed of 970 to 1000 r / min and mixing and stirring for 20 minutes to obtain a mixed slurry;
[0082] 2) The mixed mud is pressed into a brick by a press machine. The pressure of the press machine is 900t. The bulk density of the obtained brick is 2.64g / cm 3 The obtained brick blank is baked and cured at 200°C for 16 hours, and then taken out after naturally cooling to room temperature to obtain a low-carbon aluminum silicon carbide brick.
[0083] The performance of the low-carbon aluminum silicon carbide bricks prepared in each embodiment and comparative example was tested; wherein, the apparent porosity, bulk density, compressive strength at room temperature and the softening start temperature under load of 0.2MPa were tested with reference to GB / T 2997-2015, GB / T 5072-2023 and GB / T 5989-2023; the process of the thermal shock stability test was as follows: the low-carbon aluminum silicon carbide brick was made into a 40mm×40mm×160mm sample, heated to 1100°C and kept warm for 30 minutes, then taken out and quickly placed in room temperature water for rapid cooling, and the above process was repeated until the sample broke, and the number of repetitions was recorded to evaluate the thermal shock stability of the sample. The results are shown in Table 1.
[0084] Table 1
[0085]
[0086] As can be seen from Table 1, a low-carbon aluminum silicon carbide brick provided by the present invention uses dense corundum and kyanite with a specific particle size distribution, selects graphite and graphene oxide as carbon sources, and selects three additives of metal silicon powder, lanthanum oxide and zirconium carbide. Finally, a specific preparation method is adopted, and the low-carbon aluminum silicon carbide brick produced has a lower porosity. The low-carbon aluminum silicon carbide brick provided by the present invention is used as the lining of the ladle, which has excellent corrosion resistance, slag resistance and good thermal shock stability, a long service life, and energy saving and environmental protection. The preparation method of the present invention has easy-to-obtain raw materials, simple process steps, and low requirements on production equipment, and is suitable for mass production.
[0087] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A low carbon aluminum silicon carbide brick for a ladle, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of dense corundum, 10-20 parts of kyanite, 5-15 parts of silicon carbide, 3-6 parts of graphite, 3-6 parts of graphene oxide, 0.5-2 parts of metallic silicon powder, 0.5-2 parts of lanthanum oxide, 1-4 parts of zirconium carbide and 4-7 parts of phenolic resin.
2. The low carbon aluminum silicon carbide brick for ladle according to claim 1, characterized in that: The dense corundum includes the following mass proportions of dense corundum of different particle sizes: 10 to 15 parts of dense corundum with a particle size of 5 to 3 mm, 10 to 15 parts of dense corundum with a particle size of 3 to 1 mm, 10 to 15 parts of dense corundum with a particle size of 1 to 0.1 mm, and 10 to 15 parts of dense corundum with a particle size of 200 to 250 meshes.
3. The low carbon aluminum silicon carbide brick for ladle according to claim 1, characterized in that: The kyanite includes the following kyanite of different particle sizes in the following mass proportions: 3 to 6 parts of kyanite with a particle size of 3 to 1 mm, 3 to 6 parts of kyanite with a particle size of 1 to 0.1 mm, and 4 to 8 parts of kyanite with a particle size of 200 to 250 meshes.
4. The low carbon aluminum silicon carbide brick for ladle according to claim 1, characterized in that: The Al2O3 content in the dense corundum is ≥97wt%; the sum of the Al2O3 and SiO2 contents in the kyanite is ≥98wt%.
5. The low carbon aluminum silicon carbide brick for ladle according to claim 1, characterized in that: The SiC content in the silicon carbide is ≥98wt%, and the particle size is 100-120 meshes; the particle size of the graphite is 180-200 meshes; and the particle size of the graphene oxide is 180-200 meshes.
6. The low carbon aluminum silicon carbide brick for ladle according to claim 1, characterized in that: The particle size of the metal silicon powder is 180-200 meshes; the particle size of the lanthanum oxide is 260-300 meshes; and the particle size of the zirconium carbide is 80-100 meshes.
7. The low carbon aluminum silicon carbide brick for ladle according to claim 1, characterized in that: The low carbon aluminum silicon carbide brick has an apparent porosity of 8.1-8.5% and a bulk density of 2.84-2.90 g / cm 3 The room temperature compressive strength is 54.6~58.9MPa, the softening start temperature under 0.2MPa load is 1475~1490℃, and the thermal shock stability at 1100℃ water cooling is 6~8 times.
8. A method for preparing low carbon aluminum silicon carbide bricks for ladles according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Preheating dense corundum of various particle sizes, kyanite of various particle sizes, silicon carbide, graphite, graphene oxide and phenolic resin to 40-50° C. respectively; 2) adding dense corundum with a particle size of 5 to 3 mm, dense corundum with a particle size of 3 to 1 mm, kyanite and silicon carbide of various particle sizes into a mixer and stirring once, and then adding dense corundum with a particle size of 1 to 0.1 mm, dense corundum with a particle size of 200 to 250 mesh, graphite, graphene oxide, metal silicon powder, lanthanum oxide, zirconium carbide and phenolic resin and stirring twice to obtain a mixed mud; 3) The mixed mud is pressed into shape to obtain a brick blank, which is then baked and solidified to obtain a low-carbon aluminum silicon carbide brick for a ladle.
9. The method for preparing low carbon aluminum silicon carbide bricks for ladle according to claim 8, characterized in that: The stirring rate of the mixer is 970-1000 r / min, the first stirring time is 4-6 min, and the second stirring time is 10-15 min.
10. The method for preparing low carbon aluminum silicon carbide bricks for ladle according to claim 8, characterized in that: The bulk density of the brick is 2.65-2.75 g / cm 3 The curing temperature is 200-240°C and the curing time is 18-24h.
Citation Information
Patent Citations
Unfired aluminum-silicon carbide composite carbon bricks
CN109987950A
Oxidation-resistant aluminum silicon carbide carbon brick and preparation method thereof
CN113461411A
Aluminum silicon carbide carbon brick added with andalusite and preparation method of aluminum silicon carbide carbon brick
CN116217211A
Aluminum magnesia carbon brick and preparation method thereof
CN117658605A
Process for synthesis of lanthanum oxide sheets using graphene oxide
IN202341080543A